2012
DOI: 10.1029/2011gb004161
|View full text |Cite
|
Sign up to set email alerts
|

A high‐resolution ammonia emission inventory in China

Abstract: [1] The existence of gas-phase ammonia (NH 3 ) in the atmosphere and its interaction with other trace chemical species could have a substantial impact on tropospheric chemistry and global climate change. China is a large agricultural country with an enormous animal population, tremendous nitrogen fertilizer consumption and, consequently, a large emission of NH 3 . Despite the importance of NH 3 in the global nitrogen (N) cycle, considerable inaccuracies and uncertainty exist regarding its emission in China. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
463
14
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 482 publications
(518 citation statements)
references
References 91 publications
39
463
14
2
Order By: Relevance
“…This conclusion was also drawn by Liu et al, who obtained ground NH 3 concentrations in China based on satellite column density using a CTM [60]. Moreover, Liu et al concluded that the seasonal ground NH 3 concentrations were in agreement with the seasonal patterns of NH 3 emissions in China indicated by Kang et al [61], Huang et al [62], and Xu et al [63]. As shown in Figure 7, our seasonal patterns do not conform to those reported in the abovementioned studies but are well consistent with the estimations reported by Geng et al It is likely that the discrepancies in seasonal characteristics are attributed to the following factors.…”
Section: Seasonal Variations In Pm 25 Chemical Componentssupporting
confidence: 68%
“…This conclusion was also drawn by Liu et al, who obtained ground NH 3 concentrations in China based on satellite column density using a CTM [60]. Moreover, Liu et al concluded that the seasonal ground NH 3 concentrations were in agreement with the seasonal patterns of NH 3 emissions in China indicated by Kang et al [61], Huang et al [62], and Xu et al [63]. As shown in Figure 7, our seasonal patterns do not conform to those reported in the abovementioned studies but are well consistent with the estimations reported by Geng et al It is likely that the discrepancies in seasonal characteristics are attributed to the following factors.…”
Section: Seasonal Variations In Pm 25 Chemical Componentssupporting
confidence: 68%
“…Similarly, both wind speed and PBL height diminished from daytime to nighttime, with from 2.53 to 1.77 m s -1 and from 0.50 to 0.22 km for wind speed and PBL height, respectively. Hence, the morning NH 3 peak could be due to emissions from dew evaporation with increasing temperature around sunrise; enhanced release from biological sources in the city such as human excreta, waste disposal, and vegetation; and also regional diffusion from adjacent suburbs (Huang et al, 2012). In late morning and afternoon, the development of PBL height, i.e., dilution effect, as well as high wind speed, would be the reason for the decrease trend of NH 3 during that time period.…”
Section: Nh 3 Concentration and Its Temporal Variationmentioning
confidence: 99%
“…The weekday versus weekend differences in NH 3 profiles indicated that vehicular emission had a relatively small impact on ambient NH 3 at the measurement site, which was consistent with the ammonia emission inventories of Beijing. According to Huang et al (2012) and , more than 60% of total ammonia emission in Beijing comes from livestock and farm-land. Other sources, including human excrement, waste disposal, biomass burning, chemical industry and traffic, totally contributed 14.9-35.5% to the total budget with vehicular source accounting for only about 5%.…”
Section: Nh 3 Concentration and Its Temporal Variationmentioning
confidence: 99%
“…We use monthly anthropogenic emissions of NO x and SO 2 from Zhang et al [2009]. NH 3 emissions are from Streets et al [2003], with a reduction of 30% as recommended by Huang et al [2012aHuang et al [ , 2012b for Asia, and seasonality as implemented by Fisher et al [2011]. Errors in the model representation of too shallow nighttime mixing depths and overproduction of HNO 3 are corrected following Heald et al [2012] and Walker et al [2012].…”
Section: Model Descriptionmentioning
confidence: 99%
“…Such high aerosol concentrations could reduce life expectancy by several years [Lim et al, 2012]. A large fraction of the aerosol mass in Asia is composed of secondary inorganic ions as sulfate (SO 4 2À ), nitrate (NO 3 À ), and ammonium (NH 4 + ) [Huang et al, 2012a[Huang et al, , 2012b. Emission control strategies are complicated by complex chemical feedbacks that affect the relation of secondary inorganic mass with precursor emissions of SO 2 , NH 3 , and NO x [Pinder et al, 2007;Wang et al, 2011Wang et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%